Indigenous cattle of Sri Lanka: Genetic and phylogeographic relationship with Zebu of Indus Valley and South Indian origin - Lokugalappatti L. G. S.; Saumya Wickramasinghe; Alexander P. A. B. D.; Kamran Abbas; Tanveer Hussain; Saravanan Ramasamy; Vandana Manomohan; Arnaud Stephane R. Tapsoba; Rudolf Pichler; Masroor E. Babar; Kathiravan Periasamy (PLoS ONE, 2023)
The present study reports the population structure, genetic admixture and phylogeography of cattle breeds of Sri Lanka viz. Batu Harak, Thawalam and White cattle. Moderately high level of genetic diversity was observed in all the three Sri Lankan zebu cattle breeds. Estimates of inbreeding for Thawalam and White cattle breeds were relatively high with 6.1% and 7.2% respectively. Genetic differentiation of Sri Lankan Zebu (Batu Harak and White cattle) was lowest with Red Sindhi among Indus Valley Zebu while it was lowest with Hallikar among the South Indian cattle. Global F statistics showed 6.5% differences among all the investigated Zebu cattle breeds and 1.9% differences among Sri Lankan Zebu breeds. The Sri Lankan Zebu cattle breeds showed strong genetic relationships with Hallikar cattle, an ancient breed considered to be ancestor for most of the Mysore type draught cattle breeds of South India. Genetic admixture analysis revealed high levels of breed purity in Lanka White cattle with >97% Zebu ancestry. However, significant taurine admixture was observed in Batu Harak and Thawalam cattle. Two major Zebu haplogroups, I1 and I2 were observed in Sri Lankan Zebu with the former predominating the later in all the three breeds. A total of 112 haplotypes were observed in the studied breeds, of which 50 haplotypes were found in Sri Lankan Zebu cattle. Mismatch analysis revealed unimodal distribution in all the three breeds indicating population expansion. The sum of squared deviations (SSD) and raggedness index were non-significant in both the lineages of all the three breeds except for I1 lineage of Thawalam cattle (P<0.01) and I2 lineage of Batu Harak cattle (P<0.05). The results of neutrality tests revealed negative Tajima’s D values for both the lineages of Batu Harak (P>0.05) and White cattle (P>0.05) indicating an excess of low frequency polymorphisms and demographic expansion. Genetic dilution of native Zebu cattle germplasm observed in the study is a cause for concern. Hence, it is imperative that national breeding organizations consider establishing conservation units for the three native cattle breeds to maintain breed purity and initiate genetic improvement programs.